TRENDS OF DEVELOPING AGRICULTURE AND SMALL AGRICULTURAL ENTERPRISES IN CONDITIONS OF NEO-INDUSTRIALIZATION AND ENHANCING PROCESSES OF INVESTMENT AND INNOVATION IN THIS SPHERE - Sergey V. Golodov; Natal'ya S. Vasilevskaya; Tatyana E. Platonova; Vera E. Afonina (Вестник Российского экономического университета имени Г. В. Плеханова)
Today’s agriculture is a complicated biotechnological and social-economic system, which consists of many interconnected elements.  Agricultural production is characterized by high capital-intensity and  power – intensity, as well as by high risk, due to this capital inflow  from other types of economic activity is difficult, while own finance  resources for conducting extended reproduction are not sufficient.  The authors investigate the approach to the developing of agriculture in today’s conditions, which includes elements of new industrialization. The analysis of statistic data of agricultural  producers’ work allows us to say that positive results in the  development of this industry can be reached by increase in investment and continuous state support. The authors study the  activity of small agricultural enterprises and private farms, their  taxation and legislative status. They highlight the issues of using the  selective method for choosing and analyzing statistic data on private farms, provide key formulas for estimating sample data for  the sum total of typical farms, big farms and especially big farms. As an example the authors provide a calculation of key indices of animal produce output in June 2016 in federal districts.